If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7n + 6 = 3(3n + 10) Reorder the terms: 6 + -7n = 3(3n + 10) Reorder the terms: 6 + -7n = 3(10 + 3n) 6 + -7n = (10 * 3 + 3n * 3) 6 + -7n = (30 + 9n) Solving 6 + -7n = 30 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 6 + -7n + -9n = 30 + 9n + -9n Combine like terms: -7n + -9n = -16n 6 + -16n = 30 + 9n + -9n Combine like terms: 9n + -9n = 0 6 + -16n = 30 + 0 6 + -16n = 30 Add '-6' to each side of the equation. 6 + -6 + -16n = 30 + -6 Combine like terms: 6 + -6 = 0 0 + -16n = 30 + -6 -16n = 30 + -6 Combine like terms: 30 + -6 = 24 -16n = 24 Divide each side by '-16'. n = -1.5 Simplifying n = -1.5
| 12.75x-15.35=3.124(2x+3) | | 2(5a-1)-4(-2a+3)= | | 21+9j+-10=-277 | | 1-6x=7+3x-8x | | y-(-75)=60 | | 13x-15=3(2x+3) | | 2x^3-12x^2-3x+192=0 | | 12x-15=3(2x+4) | | 8c=54 | | 7n+2n=81 | | 27x-1=19x+14+5x | | 4c-5+14c= | | 13=4x+-11 | | x/3=-19 | | 2(x+8)-4=2(x-7)+8 | | x-5[2x-3(x+6)]=-4(x-5) | | -11.3x=101.7 | | 3y+6=y^2 | | =6t | | 2.5-4f=10-2.5f | | (X+10)=(2x+5) | | =10y-15y | | -10=(a-1)+(a-3) | | 28=m-4 | | x^3-16y=0 | | -4(2b+1)+(9b-7)=0 | | 7j-25=2j | | 3x+1-3x-3x-1=45 | | 6+2m=-3+5m | | x^4-6x^3+10x^2-9=0 | | x^2+(3x^2-30x+25)=25 | | 2xj+3=17 |